2017
DOI: 10.1111/anu.12638
|View full text |Cite
|
Sign up to set email alerts
|

Dietary thiamin requirement of fingerlingChanna punctatus(Bloch) based on growth, protein gain, liver thiamin storage, RNA/DNA ratio and biochemical composition

Abstract: Dietary thiamin requirement of fingerling Channa punctatus was quantified by feeding casein/gelatin-based diets (450 g/kg CP; 18.39 kJ/g GE) with seven graded levels of thiamin (0, 0.5, 1, 1.5, 2, 2.5 and 5 mg/kg diet) to triplicate groups of fish (6.9 ± 0.93 cm;4.91 ± 0.62 g) for 16 weeks. Fish fed diet with 2.5 mg/kg thiamin reflected highest absolute weight gain (AWG), protein gain (PG), RNA/DNA ratio and lowest feed conversion ratio. Similarly, highest liver thiamin concentration was also recorded in fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Intensive culture of this species is limited due to the non‐availability of nutritionally adequate commercial feeds. Though several contributions exist on protein (Jindal, Yadava, Jain, & Gupta, ; Zehra & Khan, ), vitamin (Abdel‐Hameid, Khan, & Abidi, ; Zehra & Khan, , , , , ) and mineral (Abdel‐Hameid, Zehra, & Khan, ), requirements of C. punctatus , there is no publication exists on dietary isoleucine needs of fingerling C. punctatus . Hence, this study was conducted to evaluate the requirement and effects of isoleucine concentrations on growth, carcass composition, haematological and antioxidant enzyme status in C. punctatus .…”
Section: Introductionmentioning
confidence: 99%
“…Intensive culture of this species is limited due to the non‐availability of nutritionally adequate commercial feeds. Though several contributions exist on protein (Jindal, Yadava, Jain, & Gupta, ; Zehra & Khan, ), vitamin (Abdel‐Hameid, Khan, & Abidi, ; Zehra & Khan, , , , , ) and mineral (Abdel‐Hameid, Zehra, & Khan, ), requirements of C. punctatus , there is no publication exists on dietary isoleucine needs of fingerling C. punctatus . Hence, this study was conducted to evaluate the requirement and effects of isoleucine concentrations on growth, carcass composition, haematological and antioxidant enzyme status in C. punctatus .…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2015) observed maximum weight gain at a thiamine level of 44.66 mg/kg, where the carbohydrate content was 35.6% in diets for L. vannamei, which is higher than in the current study. It was found that when dietary thiamine levels are inadequate, carbohydraterich diets deplete the body's reserves more rapidly than diets rich in fats and proteins (Zehra and Khan 2018).…”
Section: Discussionmentioning
confidence: 99%
“…RNA directly participates in protein synthesis, and the metabolic rate of the body is positively correlated with the efficiency of RNA synthesis (Kumar et al, 2018). Conversely, the DNA content of genetic information carrier molecules remains stable (Zehra and Khan, 2017). Consequently, the RNA/DNA ratio, a physiological indicator of the body's protein synthesis capacity, can accurately reflect cell metabolism (Sterzelecki et al, 2021).…”
Section: Discussionmentioning
confidence: 99%